2006
DOI: 10.1002/jbm.b.30665
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable copolymer for the slow release of growth hormone expedites scarring in diabetic rats

Abstract: In many diseases wound healing is impaired. This study was designed to establish whether the healing process in diabetes could be improved using a site-specific polymer delivery system containing hGH. The system was first optimized in in vitro experiments performed on cultured fibroblasts taken from healthy and diabetic rats and then tested in an incisional wound model created in the diabetic Wistar rat. In the in vitro experiments using cultured fibroblasts, cell viability, growth, and proliferation were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Especially, we used the pellets without chondrocytes for this analysis, which might have yielded a difference in the insulin release. The usefulness of the collagen hydrogel for the carrier of drugs was shown in the applications for IFN‐α,29 IL‐2,30, 31 NGF,32–34 bFGF2, 35–38 and hGH 39. The present report has first showed that the atelocollagen hydrogel also works as the control release of insulin.…”
Section: Discussionmentioning
confidence: 57%
“…Especially, we used the pellets without chondrocytes for this analysis, which might have yielded a difference in the insulin release. The usefulness of the collagen hydrogel for the carrier of drugs was shown in the applications for IFN‐α,29 IL‐2,30, 31 NGF,32–34 bFGF2, 35–38 and hGH 39. The present report has first showed that the atelocollagen hydrogel also works as the control release of insulin.…”
Section: Discussionmentioning
confidence: 57%
“…The proangiogenic effects of GH have also been demonstrated in vivo. Treatment with GH increases the number of cerebral cortical arterioles in aging rats (515), augments VEGF expression and angiogenesis in the rat myocardium after infarction (302,468), stimulates wound angiogenesis in diabetic rats (191) and in mice (553), and may enhance vascularization by promoting mobilization ACTH 263 Adrenomedullin 460 Angiotensin II 236 Bradykinin 236 Calcitonin 89 Endothelin 218 Erythropoietin 23 Gastrin 212 Gonadotropins 457 Growth hormone/prolactin/placental lactogen 109 Growth hormone-releasing hormone 274 Insulin 270 IGF-I 129 Leptin 233 Neuropeptide Y 300 Oxytocin 79 Parathyroid hormone 389 Relaxin 202 Thrombopoietin 17 Thyroid-stimulating hormone 457 Vasopressin 13 of bone marrow-derived endothelial progenitor cells into the bloodstream (134,554). Consistent with these findings, the skin of adult, GH-deficient patients shows reduced capillary density and permeability that improves after treatment with GH (418), and GH-deficient adults and children have reduced retinal vascularization (238,239).…”
Section: Growth Hormonementioning
confidence: 99%
“…21 rHGH has been shown to be effective in closing cutaneous defects of the epithelium, accelerating wound healing, 21-23 activating epidermal and epithelial cell migration in burn victims, and assisting wound healing in diabetic rats. 24, 25 However, it is not known whether these effects of GH are mediated by IGF-1, and conflicting data have been reported regarding the roles of GH versus IGF-1 on the mechanism of increased cutaneous healing. For example, GH was reported to enhance human keratinocyte migration, promote human foreskin fibroblast expression of IGF-1 and stimulate fibroblast proliferation in vitro.…”
Section: Introductionmentioning
confidence: 99%